“Hot” executive functions are comparable across monolingual and bilingual elementary school children: Results from a study with the Iowa Gambling Task - Enke, Susanne; Gunzenhauser, Catherine; Johann, Verena E.; Karbach, Julia; Saalbach, Henrik (Frontiers in Psychology, 2022)
Past research found performance differences between monolingual and bilingual children in the domain of executive functions (EF). Furthermore, recent studies have reported advantages in processing efficiency or mental effort in bilingual adults and children. These studies mostly focused on the investigation of “cold” EF tasks. Studies including measures of “hot” EF, i.e. tasks operating in an emotionally significant setting, are limited and hence results are inconclusive. In the present study, we extend previous research by investigating performance in a task of the “hot” EF domain by both behavioral data and mental effort via pupillary changes during task performance. Seventy-three monolingual and bilingual school children (mean age = 107.23 months, SD = 10.26) solved the Iowa Gambling Task in two different conditions. In the standard task, characterized by constant gains and occasional losses, children did not learn to improve their decision-making behavior. In a reversed task version, characterized by constant losses and occasional gains, both monolinguals and bilinguals learned to improve their decision-making behavior over the course of the task. In both versions of the task, children switched choices more often after losses than after gains. Bilinguals switched their choices less often than monolinguals in the reversed task, indicating a slightly more mature decision-making strategy. Mental effort did not differ between monolinguals and bilinguals. Conclusions of these findings for the bilingual advantage assumption will be discussed.